Geospatial Technology and Smart Cities
XVIII, 497 p. 204 illus., 179 illus. in color.
Keywords: This book presents fundamental and applied research in developing geospatial modeling solutions to manage the challenges that urban areas are facing today. It aims to connect the academics, researchers, experts, town planners, investors and government officials to exchange ideas. The areas addressed include urban heat island analysis, urban flood vulnerability and risk mapping, green spaces, solar energy, infrastructure management, among others. The book suggests directions for smart city research and outlines practical propositions. As an emerging and critical area of research and development, much research is now being done with regard to cities. At the international level and in India alike, the “smart cities” concept is a vital topic for universities and research centers, and well as for civic bodies, town planners and policymakers. As such, the book offers a valuable resource for a broad readership.